Small Folklore Forms in the Life of Signatory Petras Klimas - Kašėtienė, Rasa (Tautosakos darbai, 2018)
The 100th anniversary of the Lithuanian independence prompts one to remember the members of the Council of Lithuania who signed the Act of Independence of Lithuania on February 16, 1918. Among them, there was a lawyer, historian, journalist, editor and diplomat, the future Minister of Foreign Affairs of the Republic of Lithuania – Petras Klimas (1891–1969), who very significantly contributed to establishing of the independent Lithuanian state. Klimas published his first articles and a humorous essay “Christmas Is Fun for Some but Trouble for Others” as early as 1908, while still studying at the Marijampolė Gymnasium. He signed those pieces by pseudonym Vabalėlis (‘little beetle’), since at that time he felt particularly fascinated with texts by a left-wing journalist Albertas Vabalas-Prūseika. Therefore, Klimas used the above-mentioned pseudonym until 1913, relinquishing it afterwards. Klimas became actively engaged in the Lithuanian Science Society, which aimed at encouraging the intelligentsia to join in various cultural initiatives and take part in preservation of the national cultural heritage, promoting interest in local history and native language. Among other things, Klimas was interested in small forms of Lithuanian folklore. This is evident from a little (nine pages long) manuscript collection of proverbs, still preserved at the Lithuanian Folklore Archives and marked LMD I 858. This collection, compiled by Petras Klimas – Vabalėlis contains 244 items belonging to this folklore genre. Klimas listed proverbs (144) separately from proverbial phrases (100), explaining the difference between them in a short introduction to his collection. Already in his first publications, Klimas seemed apt at using proverbs and proverbial phrases properly and according to the situation. Apparently, the signatory-to-be knew a lot of them and willingly inserted them in his speech for added playfulness and figurativeness. Klimas enthusiastically contributed to editing of the periodical “Aušrinė”. As a university student, he published 16 articles there. Editing texts for the Lithuanian periodicals helped Klimas to improve his literacy skills in Lithuanian, which became very handy somewhat later, when he started working in the Commission for Textbooks established by the Lithuanian Science Society. Klimas led an interesting, rich and colorful life with many complicated turns: from attending the Marijampolė Gymnasium to very important, tough and stressful work at establishing the Lithuanian independence. Subsequently Klimas worked as a Lithuanian diplomat and suffered at Nazi prisons and Soviet deportation camps. However, he did not crack even in the most difficult situations, still upholding his principles and denouncing the Soviet regime openly and boldly.